Comparison of the efficacy of crude methanolic extracts of Cassia occidentalis and Euphorbia hirta with levamisole-HCL against gastrointestinal nematodes of economic importance to goat production in Uganda - Nsereko, Godfrey; Emudong, Patrick; Omujal, Joseph; Acai, James; Kungu, Joseph M.; Kabi, Fredrick; Mugerwa, Swidiq; Bugeza, James (Tropical animal health and production, 2019)
Natural compounds from medicinal plants provide safe and sustainable alternatives to synthetic anthelmintics. In this study, we assessed in vitro and in vivo anthelmintic activity of Cassia occidentalis (NH-A) and Euphorbia hirta (NH-B) and compared it with levamisole-HCl. The shoots of NH-A and whole plant of NH-B were used to prepare extracts using 70% methanol which were used in the in vitro and in vivo assays. In vitro assays of crude methanolic extracts (CMEs) of NH-A and NH-B on larvae of mixed gastrointestinal nematodes (GINs) of goats revealed mortalities of 95.7%(at 100 mg ml−1) and 98.1%(at 50 mgml−1) 24 h postexposure. In vivo assays of NH-A administered orally at doses of 100, 300, 900, and 2700 mg kg−1 bwt revealed dose- and time-dependent anthelmintic effects in goats experimentally infected with mixed species of GINs. NH-B exhibited similar properties when administered at doses of 50, 100, 200, and 400 mg kg−1 bwt. Both NH-A (900 mg kg−1 bwt) and levamisole (7.5 mg kg−1 bwt) achieved a 100% reduction in fecal egg count per gram (EPG) on day 21 and day 14 respectively posttreatment. NH-B (400 mg kg−1 bwt) achieved 93.1% and 86.1% reduction in fecal EPG 7 and 14 days postexposure respectively compared with 88.2% and 82.3% reduction with levamisole-HCl 7 and 14 days postexposure. Our results show that extracts of both plants can disrupt helminth lifecycles by suppressing the egg-laying capacity in adult worms but also kill their infective larvae. Future studies should aim at establishing synergies or antagonisms between the two plant extracts and further development for control of helminths in goats.
Keywords: Helminths; Natural products; Agro-ecological zones; Cassia occidentalis; Euphorbia hirta